2018
DOI: 10.5152/eurasianjmed.2018.17237
|View full text |Cite
|
Sign up to set email alerts
|

Increased Iron Deficiency and Iron Deficiency Anemia in Children with Zinc Deficiency

Abstract: Objective: The aim of the present study is to determine the presence of iron (Fe) deficiency and Fe deficiency anemia in children with zinc (Zn) deficiency. Materials and Methods: This retrospective study comprised 560 patients aged 6 months to 16 years in whom Zn levels in hair samples were measured concurrently with serum levels of ferritin, Fe, Fe-binding capacity, and blood count analysis. For all patients, we retrospectively assessed serum ferritin, serum Fe, Febinding capacity, transferrin saturation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Similarly, a large cross-sectional study among pregnant women ( n = 1185) found low serum zinc levels among anemic subjects, and furthermore, serum zinc levels were significantly and positively correlated with hemoglobin [13]. Other studies have shown that the plasma zinc levels were significantly lower among subjects with iron deficiency anemia [12,13]. In addition, low serum zinc reported to be an independent risk factor for anemia among school-age children in New Zealand [14].…”
Section: Impact Of Zinc Deficiency On Iron Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a large cross-sectional study among pregnant women ( n = 1185) found low serum zinc levels among anemic subjects, and furthermore, serum zinc levels were significantly and positively correlated with hemoglobin [13]. Other studies have shown that the plasma zinc levels were significantly lower among subjects with iron deficiency anemia [12,13]. In addition, low serum zinc reported to be an independent risk factor for anemia among school-age children in New Zealand [14].…”
Section: Impact Of Zinc Deficiency On Iron Statusmentioning
confidence: 99%
“…Clinical studies in human subjects indicated that serum zinc levels correlate with iron status markers. Hemoglobin, plasma ferritin, mean corpuscular volume (MCV), and red cell distribution width (RDW) were found to be higher in zinc sufficient (>100 µg/dL) compared to zinc deficient (<100 µg/dL) subjects [12]. Similarly, a large cross-sectional study among pregnant women ( n = 1185) found low serum zinc levels among anemic subjects, and furthermore, serum zinc levels were significantly and positively correlated with hemoglobin [13].…”
Section: Impact Of Zinc Deficiency On Iron Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…The zinc-deficient diet increased plasma hepcidin level, consistent with reduced intestinal iron absorption (109). There might be a physiological crosstalk between iron and zinc in erythropoiesis because clinical studies revealed that patients with iron deficiency anemia were significantly associated with zinc deficiency (110,111). Moreover, zinc supplementation stimulates erythropoiesis while zinc plus iron more efficiently ameliorated anemia than iron alone (112,113).…”
Section: Zincmentioning
confidence: 95%
“…7 Apprehension and increased parental anxiety due to seizures is found in 2%-4% patients. 8 It puts a burden of cost on the family, society and health system. There is high chance of recurrence of seizures with the frequency of 30% after first episode and 50% after second episode of seizures.…”
Section: Introductionmentioning
confidence: 99%